Notch signaling: A potential target for the development of host-directed therapies against tuberculosis - Baindara, Piyush (Frontiers in Tropical Diseases, 2023)
Tuberculosis (TB) is one of the preeminent causes of death among infectious diseases and remains a global threat to human health. Mycobacterium tuberculosis (Mtb) has coevolved with the human host and is an extremely successful pathogen by abusing the human system in different ways. Interestingly, Mtb can remain undetected in the human host for years as latent TB, so there is an urgent need to develop new therapies to combat Mtb. In the recent past, host-directed therapies have attracted the research community as a promising approach to combat TB, and thus novel host targets are of interest. In the present editorial, we have explored and suggested Notch signaling as a potential host target to develop a new therapeutic strategy against Mtb.